Experimental program on the burst capacity of reinforced thermoplastic pipe (RTP) under impact of quasi-static lateral load - Bakar, M.A.A. (Elsevier Ltd, 2021)
Reinforced Thermoplastic Pipe (RTP) is a flexible composite pipe that currently receives fair acceptance in the oil and gas industry, with high potentials to be used as a replacement to the carbon steel (CS) pipes especially in high corrosive environment. As RTP is relatively new products, their designs and qualifications are governed by the industry practice at present in the absence of comprehensive technical design standards. Most literatures to date are mainly dedicated to the intact RTPs, while the response of the pipe towards various defects have not been fully understood. Quite often, the assessments are made by referring to the design standards of the CS pipes, which are not entirely suitable due to the flexible characteristics of the composite pipe itself. Thus, this paper aims at assessing the performance of a 4â³ RTP when exposed to lateral loads from external interferences such as the anchor dropped. Herein, the damaged to the RTP pipe was made in the form of a dent indented by a cylindrical conical nose under the quasi-static indentation procedures carried out experimentally. The damaged or dented pipe was later tested for its burst capacity using a burst testing facility specially fabricated for composite pipes. During the experiments, two types of failure modes were observed, namely single unit and ply-by-ply failures. Outcomes obtained from the experiments were used to describe the relationships between three important parameters, namely lateral load, indentation depth and burst pressure using polynomial regression equations. These simplified equations may be adopted directly in pipeline assessments and operations of RTP pipes exposed to dents. Moreover, outcomes from this paper will be beneficial in qualifying further RTP as a new free-corrosion risk transportation system for the oil and gas industry. Â© 2021 Elsevier Ltd